Influência do etil-trinexapac no crescimento inicial do eucalipto - Pires, Rodrigo Neto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Aiming to establish inhibitory and promoters doses of trinexapac-ethyl applied in two methods, as well evaluate the effects on the initial growth of eucalyptus plantas three experiments were conduct in Jaboticabal city. Experiments 1 and 2 were conduct in an annexed area of the Laboratory of Biology and Weed Management at the Faculty of Applied Biology to Agriculture. These experiments were conduct, respectively, between February - April 2013 and February – April 2014. The experiment 3 was conduct in the field belonging to the University Farm also in Jaboticabal city between the months of September 2013 and March 2014. The treatments of the experiments 1 and 2 consisted in application of trinexapac-ethyl doses (0; 2.5; 5; 7.5; 10; 12.5; e 15 g i.a.ha-1 and 0, 15, 30, 45, 60, 75, e 90 g i.a.ha-1, respectively) by spraying and root immersion. The experimental design used was the completely randomized with six replications in a factorial 2 x 7. Were evaluated height, stem diameter, number of leaves, leaf area, and root volume as well dry mass of shoot, roots and total. Results showed in the experiment 1, that trinexapac-ethyl doses were not capable to differentiate promoters and inhibitory effects on the development of eucalyptus plants. In experiment 2, results showed that 15 g i.a. ha-1 dose applied through spraying and 30 g i.a. ha-1 dose of trinexapac-ethyl applied through root immersion, for 30 min, caused hormesis of the eucalyptus plants development. From the 45 g i.a. ha-1 dose applied through root immersion the effects started to result in harmful outcomes to the eucalyptus plants and the 90 g i.a. ha-1 dose was highlight because decreased the eucalyptus development in both application methods. Differences between the effects of the application methods was observed and the spraying results were faster and short term effects while the results of roots immersion (for 30 min) were intense and long term effects. In the experiment ...

Com o objetivo de determinar doses promotoras e inibidoras de etil-trinexapac em duas modalidades de aplicação, bem como os efeitos da aplicação do produto sobre o crescimento do eucalipto foram conduzidos três experimentos localizados no município de Jaboticabal, SP. Os experimentos 1 e 2 foram conduzidos em área anexa ao Laboratório de Biologia e Manejo de Plantas Daninhas, no Departamento de Biologia Aplicada a Agropecuária da Faculdade de Ciências Agrárias e Veterinárias – FCAV/UNESP entre os meses de Fevereiro – Abril de 2013 e Feveiro – Abril de 2014 respectivamente. O experimento 3 foi conduzido em área da Fazenda de Ensino, Pesquisa e Extensão – FEPE pertencente a FCAV/UNESP também em Jaboticabal, SP entre os meses de Setembro de 2013 e Março de 2014. Os tratamentos dos experimentos 1 e 2 constaram de aplicações de etil-trinexapac nas doses de 0; 2,5; 5; 7,5; 10; 12,5; e 15 g i.a.ha-1 e 0, 15, 30, 45, 60, 75, e 90 g i.a.ha-1, respectivamente, aplicadas via pulverização foliar e imersão de raízes. O delineamento experimental utilizado foi o inteiramente casualizado com seis repetições arranjados no esquema fatorial 2 x 7. Foram avaliadas a altura, diâmetro do caule, número de folhas, área foliar, volume radicular, bem como a massa seca da parte aérea, raízes e total. Observou-se que as doses de etil-trinexapac, no experimento 1, não foram suficientes para a determinação de doses promotoras e inibidoras do desenvolvimento das plantas de eucalipto. Verificou-se também que, no experimento 2, a dose de 15 g i.a. ha-1 via pulverização foliar e de 30 g i.a. ha-1 via imersão de raízes, por 30 minutos, resultaram em efeito hormético no crescimento do eucalipto clone GG 100 e que a partir da dose 45 g i.a. ha-1 o efeito da imersão passou a ser prejudicial às plantas, destacando que a dose de 90 g i.a. ha-1 de etil-trinexapac que resultou efeito inibidor do crescimento para ambas as modalidades ...
Keywords: Eucalipto; Eucalipto - Maturação; Crescimento (Plantas); Reguladores de crescimento; Produtos químicos agrícolas; Growth (Plants)